If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (C + -4) + (3c + 9) = 0 Reorder the terms: (-4 + C) + (3c + 9) = 0 Remove parenthesis around (-4 + C) -4 + C + (3c + 9) = 0 Reorder the terms: -4 + C + (9 + 3c) = 0 Remove parenthesis around (9 + 3c) -4 + C + 9 + 3c = 0 Reorder the terms: -4 + 9 + C + 3c = 0 Combine like terms: -4 + 9 = 5 5 + C + 3c = 0 Solving 5 + C + 3c = 0 Solving for variable 'C'. Move all terms containing C to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + C + -5 + 3c = 0 + -5 Reorder the terms: 5 + -5 + C + 3c = 0 + -5 Combine like terms: 5 + -5 = 0 0 + C + 3c = 0 + -5 C + 3c = 0 + -5 Combine like terms: 0 + -5 = -5 C + 3c = -5 Add '-3c' to each side of the equation. C + 3c + -3c = -5 + -3c Combine like terms: 3c + -3c = 0 C + 0 = -5 + -3c C = -5 + -3c Simplifying C = -5 + -3c
| -8=24+y | | 8=2(v+3) | | x*x*x*x=20 | | -2(3s-6)-12=-3(5s+-1)-5 | | 34-r=18 | | 1/2(4x+8)=1/5(15-20x) | | E-7=10 | | 2x+3x+4x=65 | | 25=5x+15 | | x-10-5=14 | | 2X^2+32X+32=0 | | 5a+7b-4a-9b+2x= | | 16-y=8 | | 8x+23=35 | | -7/9y=-6 | | 3(x+7)=9-2x | | .7w-.4w+.2w=4 | | 5x=5-25 | | 5x^2y/15x^3y | | 5(1)=5-25y | | x^6+x^4-2x^2-8= | | 3a+5b-8b+2a= | | 12x+6=10+4x | | 3x/-2=6 | | .67x-.72x=5 | | 2/3x-5/7x=5 | | .60+.05(8-x)=.10(-29) | | 7r-15r=16 | | 2/9/1/2 | | 12-1.7v=4.15 | | 2/9/1/9 | | 7x^2+24x-16=0 |